7th International Immunoglobulin Conference: Neurology. (December 2014) - Nobile‐Orazio, E.; Lewis, R. A.
Summary: Data presented demonstrate the versatility of immunoglobulin (Ig) therapy for a variety of neurological disorders with different pathogenesis and presentations. In indications where the efficacy of Ig is well established, the neurology community is striving to improve the use of this valuable and limited resource by perfecting best practice guidelines, individualizing dosing schemes and investigating combination therapies to enhance treatment benefit. The data showing the efficacy of Ig therapy in conditions such as chronic pain and autoimmune encephalitis are promising. Future challenges for Ig use in neurological disorders were also outlined. Ongoing and upcoming randomized controlled trials will be pivotal to the use of Ig in the future, by identifying responder groups and elucidating the most effective administration practices. As our understanding and use of the therapy increases, it is essential that we collect data on the effects of long‐term Ig treatment in neurological conditions, of which very little currently exists.